Bridging the Trust Gap : Blockchain’s Potential to Restore Trust in Artificial Intelligence in Support of New Business Models - Niforos, Marina (International Finance Corporation, Washington, DC, 2020)
Rapid increases in computing power and data generation have turned artificial intelligence, blockchain, and the Internet of Things into potent technologies that are rapidly gaining use in many areas of society and commerce, with significant potential benefits for economic growth and development. These innovative technologies face multiple obstacles to implementation and, particularly in the case of AI, a general wariness of their potential implications for human society. Fortunately, an integrated implementation of the three technologies may be a solution that can restore human trust in AI and blockchain applications, resulting in new business models that deliver data security and privacy, efficiency, and inclusion along with their many other benefits.